2022
DOI: 10.1186/s40066-022-00388-z
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of a home garden intervention in Bangladesh after one, three and six years

Abstract: Background Training women in home gardening and nutrition has been shown to increase household production and consumption of nutritious food and contribute to women’s empowerment, but evidence is limited to short-term effects. Here, we investigate whether home garden support leads to long-term improvements in household nutrition and women’s empowerment. To do this we use four waves of household-level survey data collected over a 7-year period (2013–2019) from an intervention (n = 395) and a con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
15
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(16 citation statements)
references
References 25 publications
1
15
0
Order By: Relevance
“…This result is plausible and consistent with the results of previous studies which have shown that home gardens contribute to improved dietary diversity and food security (Blakstad et al, 2021;Rammohan et al, 2019). Overall, the results in Table 4 show evidence of the positive effects of home gardens on food security and are consistent with previous literature which suggested that home gardens can contribute to improved food security by increasing production (food availability), consumption of home-produced foods and dietary diversity (Baliki et al, 2022;Blakstad et al, 2022;Depenbusch et al, 2022;Rammohan et al, 2019).…”
Section: Effects Of Home Gardens On Food Securitysupporting
confidence: 90%
See 1 more Smart Citation
“…This result is plausible and consistent with the results of previous studies which have shown that home gardens contribute to improved dietary diversity and food security (Blakstad et al, 2021;Rammohan et al, 2019). Overall, the results in Table 4 show evidence of the positive effects of home gardens on food security and are consistent with previous literature which suggested that home gardens can contribute to improved food security by increasing production (food availability), consumption of home-produced foods and dietary diversity (Baliki et al, 2022;Blakstad et al, 2022;Depenbusch et al, 2022;Rammohan et al, 2019).…”
Section: Effects Of Home Gardens On Food Securitysupporting
confidence: 90%
“…Second, many previous studies rely on cross-sectional data which are limited for drawing robust causal inference. Notable exceptions include studies by Olney et al (2015Olney et al ( , 2016, Schreinemachers et al (2016), Osei et al (2017), Baliki et al (2019Baliki et al ( , 2022, Blakstad et al (2021Blakstad et al ( , 2022, and Depenbusch et al (2021Depenbusch et al ( , 2022, that used experimental or quasi-experimental designs with panel data. Lastly, studies analysing the effects of agricultural interventions on nutritional outcomes in India, other parts of South Asia, and among the most vulnerable population groups are limited (Bird et al, 2019;Kadiyala et al, 2014;Pandey et al, 2016;Rammohan et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Nevertheless, the papers dealing with the nutritional function of gardens from a quantitative point of view are relatively few. Most of them are referred to poor rural areas of some Asian countries, like India, Bangladesh, and Cambodia (Schreinemachers, Patalagsa and Uddin, 2016; Singh, Singh and Singh, 2018; Borthakur et al, 2021; Baliki et al, 2022; Depenbusch et al, 2022; Singh et al, 2022). These studies focus on the fact that the establishment of a food garden and the engagement of women in home gardening and nutrition training programs increased vegetables consumption and consequently the nutrient intake of the families involved.…”
Section: Resultsmentioning
confidence: 99%
“…Zooming out of conflict and crises setting, there is a significant body of literature that studies the theoretical and empirical links between agriculture and nutrition, yet strong causal evidence of the effectiveness of targeted agricultural intervention on production and consumption in developing settings remains inconclusive (Ruel et al, 2018). A number of studies show that agricultural interventions improve diet diversity and quality and thus micronutrient status (Baliki et al, 2022b;Mary et al, 2020;Rutherford et al, 2016;Schreinemachers et al, 2020). Interventions that incorporate multiple aspects of nutrition education and health such as improvement in WASH practices, health access, and the provision of fortified products along with the agricultural intervention may be more effective than agricultural interventions alone, especially for improving nutrition and longterm health (Doocy et al, 2019).…”
Section: The Impact Of the War In Syriamentioning
confidence: 99%